2014
DOI: 10.3389/fgene.2014.00268
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic ionizing radiation exposure results in expression alterations of genes associated with cardiovascular and neurological development, function, and disease and modified cardiovascular function in zebrafish

Abstract: The relationship between ionizing radiation (IR) and carcinogenesis is long established, but recently the association between IR and other diseases is starting to be recognized. Currently, there is limited information on the genetic mechanisms governing the role of IR in non-cancer related adverse health effects and in regards to an early developmental exposure. In this study, zebrafish embryos were exposed to a range of IR doses (0, 1, 2, 5, 10 Gy) at 26 h post fertilization (hpf). No significant increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 72 publications
3
21
0
Order By: Relevance
“…Our initial experiment showed that <3 hpf embryos were extremely sensitive to IR (data not shown), 1 Gy IR increased mortality and a dose-dependent mortality rate was observed (Figure 1a-c). Our findings are consistent with other reports on the early development stages and IR toxicity (Freeman, Weber, Peterson, & Nie, 2014;Geiger et al, 2006;T. C. Pereira, Rico, et al, 2011), where the lethal effects of IR were inversely related to embryonic age.…”
Section: Discussionsupporting
confidence: 94%
“…Our initial experiment showed that <3 hpf embryos were extremely sensitive to IR (data not shown), 1 Gy IR increased mortality and a dose-dependent mortality rate was observed (Figure 1a-c). Our findings are consistent with other reports on the early development stages and IR toxicity (Freeman, Weber, Peterson, & Nie, 2014;Geiger et al, 2006;T. C. Pereira, Rico, et al, 2011), where the lethal effects of IR were inversely related to embryonic age.…”
Section: Discussionsupporting
confidence: 94%
“…Target primer sequences were forward , reverse . Similarly to previous studies β-actin was found to be the most consistent and least variable control for this analysis [31]. The primer sequence for β-actin was the same as used in a previous study [32] forward and reverse .…”
Section: Methodsmentioning
confidence: 87%
“…Fluorescence signal intensities were normalized using quantile normalization (Bolstad et al 2003) and gene calls generated using the Robust Multichip Average algorithm (Irizarry et al 2003) following manufacturer recommendations. Array image data was analyzed as previously described (Freeman et al 2014; Peterson et al 2011; Weber et al 2013). A robust and reproducible list of differentially expressed genes for each atrazine treatment using recommendations from the Microarray Quality Consortium (Guo et al 2006; Shi et al 2006) was first determined by genes consistently expressed using an ANOVA in SAS software (p<0.05) and substantially altered with a mean absolute log 2 expression ratio of at least 0.585 (50% increase or decrease in expression).…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
“…A robust and reproducible list of differentially expressed genes for each atrazine treatment using recommendations from the Microarray Quality Consortium (Guo et al 2006; Shi et al 2006) was first determined by genes consistently expressed using an ANOVA in SAS software (p<0.05) and substantially altered with a mean absolute log 2 expression ratio of at least 0.585 (50% increase or decrease in expression). Each gene list was imported into Ingenuity Pathway Analysis (IPA) for gene ontology and molecular pathway analysis following similar parameters as described previously (Freeman et al 2014; Peterson et al 2011; Weber et al 2013). Genes referred to in the results and discussion sections are represented as the human homologs of the genes identified to be altered by microarrays.…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation